"I don't want to be known for that:"The role of temporality in online self-presentation of young gay and bisexual males. (May 2021) - Birnholtz, Jeremy; Macapagal, Kathryn
Abstract: Self-presentation, the social process by which people reveal information about themselves and perform the social roles that structure everyday interactions, has been significantly altered by today's social technologies. Where Goffman's influential self-presentation framework focused on in-person, real-time role performances, today's technologies routinely involve viewing text and visual content aggregated over time and linked to an individual's persistent online identity, the capacity for both ephemeral and more permanent content, and novel modes of audience engagement such as liking and commenting. These new socio-technical affordances not only allow for novel behaviors, but also alter the temporal dynamics of the self-presentation process in ways that are not well understood. In this paper we address this gap through an interview study of 32 young gay and bisexual male (GBM) Instagram users in the United States. Results extend our understanding of the relationship between social technology affordances and the temporal dynamics of self-presentation. We show how participants drew on Instagram's affordances for identity persistence, content persistence and audience engagement to slow down or speed up their role performances to particular audiences, to increase the visibility of their performances without appearing overtly to seek attention, and to make their audience at any given point in time a part of the performance seen by future audiences. Highlights: Unlike in-person, performing social roles online can occur across multiple time scales. The temporality of online affordances and self-presentation are interrelated and used strategically by participants. Audience plays a novel role in social media self-presentation, akin to extras on a film set.